DamID in C. elegans reveals longevity‐associated targets of DAF‐16/FoxO - Eugene Schuster; Joshua J McElwee; Jennifer M A Tullet; Ryan Doonan; Filip Matthijssens; John S Reece‐Hoyes; Ian A Hope; Jacques R Vanfleteren; Janet M Thornton; David Gems (Molecular Systems Biology, 2010)
Abstract Insulin/IGF‐1 signaling controls metabolism, stress resistance and aging in Caenorhabditis elegans by regulating the activity of the DAF‐16/FoxO transcription factor (TF). However, the function of DAF‐16 and the topology of the transcriptional network that it crowns remain unclear. Using chromatin profiling by DNA adenine methyltransferase identification (DamID), we identified 907 genes that are bound by DAF‐16. These were enriched for genes showing DAF‐16‐dependent upregulation in long‐lived daf‐2 insulin/IGF‐1 receptor mutants (P=1.4e−11). Cross‐referencing DAF‐16 targets with these upregulated genes (daf‐2 versus daf‐16; daf‐2) identified 65 genes that were DAF‐16 regulatory targets. These 65 were enriched for signaling genes, including known determinants of longevity, but not for genes specifying somatic maintenance functions (e.g. detoxification, repair). This suggests that DAF‐16 acts within a relatively small transcriptional subnetwork activating (but not suppressing) other regulators of stress resistance and aging, rather than directly regulating terminal effectors of longevity. For most genes bound by DAF‐16∷DAM, transcriptional regulation by DAF‐16 was not detected, perhaps reflecting transcriptionally non‐functional TF ‘parking sites’. This study demonstrates the efficacy of DamID for chromatin profiling in C. elegans.